Local Government Councils Performance and the Quality of Service Delivery in Uganda Nebbi District Council Scorecard 2008/09 - Tamale, Lillian Muyomba; Owor, Arthur; Kumakech, James; Rupiny, Ronnie Robert (ACODE Policy Research Series, 2010)
In 1992, Uganda adopted a decentralization policy that sought to establish a system of governance underpinned by strong local governments. Subsequent constitutional and legal reforms established districts and sub-counties as key pillars of local governments through which effective service delivery and local governance is to be attained. Although decentralization has been pursued over the last two decades, there is widespread consensus that the performance of local governments is less than desirable. The revenue base of local governments has diminished substantially, rendering them heavily dependent on central government disbursements, mainly through conditional grants. The quality of service provision is less than desirable, as well, with key services such as health care, water, sanitation, education, and access to agricultural advisory services remaining dismal. Yet, there is no evidence that the citizens who are the intended beneficiaries of the decentralization system are demanding accountability and better performance from their elected leaders. Over the years, the Ugandan government has sought to improve the functioning of local governments through regular monitoring and inspection processes. However, these processes have not adequately focused on the local government councils, as the mandated executive and legislative organs of the local governments. This report is a product of an ongoing assessment of the performance of local government councils in Uganda that commenced in 2009, focusing on the financial year 2008/09. The assessment was designed as part of an initiative to regularly monitor the performance of local government councils in Uganda, and to publish and disseminate a local councils performance “score-card” as a means of increasing citizens’ demand for improved service delivery and accountability on the part of elected leaders. For the FY2008/09, similar assessments were undertaken in nine other districts including Amuria, Amuru, Hoima, Kampala, Kamuli, Luwero, Mbale, Moroto, and Ntugamo. The assessment focused on the local government councils and their respective organs as outlined in the Local Government Act and other legislation. The council as a corporate body, the chairperson, the speaker, and the councilors formed the units of analysis for the assessment.